Diagnóstico geoambiental da sub-bacia hidrográfica do Rio Figueiredo, Ceará: subsídios ao planejamento ambiental - Sousa, Maria Losângela Martins de (2012)
This research approaches the issue of integrated studies as an aid to environmental planning, having as the case study the sub-basin of the Rio Figueiredo. This river is one of the main tributaries of the Jaguaribe drainage basin, located in the eastern portion of the state of Ceara, Brazil. It has as its main objective to conduct an environmental analysis of the integrated sub-basin, highlighting the carrying capacity of its natural resources and ways to use and occupation, with a view to supporting environmental planning. For this purpose, its specific objectives are: to identify the environmental systems and types of use and occupation of their natural resources to investigate the main environmental problems in the sub-basin set, relating the causes and consequences; make a list of the floristic composition of the environmental systems aiming to realize the environmental degradation from the loss of biodiversity. This research was structured in three main stages. The first one is focused on documentary research, as well as the collection of complementary data on the study area. The second concerns the collecting of the geocartographic base data and satellite images. The third will discuss a practical field work through the interpretation of satellite images and cartographic production. The main results showed that the sub-basin has four environmental systems: fluvial plains and areas of seasonal flooding, depression hinterland, which is divided in the backlands of Alto Santo, Iracema/Potiretama, Pereiro/Ererê, residual ridges, Pereiro residual massive and the heights of the Apodi plateau. This sub-basin presents processes of environmental degradation and desertification risk, because it has semi-arid climatic conditions and human activities that compromise the carrying capacity of its natural resources, including livestock, agriculture and extraction plant, whose techniques are unsuitable for use. In this context, the recognition of the potential and limitations of the natural area is of great importance to the environmental guidelines.